2006
DOI: 10.1016/j.otohns.2005.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Hearing Loss and Otopathology in Cleft Palate Patients

Abstract: C-4 SIGNIFICANCE: Cleft palate children requiring multiple tube insertions should be monitored closely for CHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
2
17

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 20 publications
7
91
2
17
Order By: Relevance
“…Therefore the sex distribution is likely due to the predomi- 123 nance of this type of cleft in the studied sample. This sex distribution does not correlate with that reported by other studies, which have reported a female preponderance [4][5][6]. The reason for this is likely to be a difference in the sample studied.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Therefore the sex distribution is likely due to the predomi- 123 nance of this type of cleft in the studied sample. This sex distribution does not correlate with that reported by other studies, which have reported a female preponderance [4][5][6]. The reason for this is likely to be a difference in the sample studied.…”
Section: Discussioncontrasting
confidence: 96%
“…2% ears were diagnosed with acute otitis media, and 1% had chronic otitis media of the squamous type. The prevalence of acute and chronic otitis media is less than 5 to 6% reported by other investigators [4,5]. This is probably explained by the fact that the studied sample consisted of children predominantly in the age group of one to three years.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Although the likelihood of developing OME is reduced after reaching adulthood, it is estimated that 50% of these children suffer from permanent conductive hearing loss [21,22]. Additionally, 0.9-5.9% of patients with CLP develop primary acquired cholesteatoma, the probability of which is 100-200 times higher among those without CLP [23,24].…”
Section: Consequences Of Ome In Clpmentioning
confidence: 99%
“…Many studies have indicated that although reconstructive surgery for CLP improves linguistic ability, language development depends on the extent to which hearing ability is maintained [23,26]. If OME is not treated properly, long-term hearing loss can negatively influence the language development of children [27].…”
Section: Consequences Of Ome In Clpmentioning
confidence: 99%